Katniss Everdeen’s Character Development in Suzanne Collins' The Hunger Games Trilogy - Valeri Putri Mentari Ardi; Bernadus Hidayat (Universitas Gadjah Mada, 2018)
This research examines the character development of Katniss Everdeen, the protagonist in Suzanne Collins’ The Hunger Games trilogy. It attempts to investigate whether socioeconomic factors play a role in Katniss’s character development. To address this question, Marxism was adopted as the theoretical framework to analyze Katniss’s character development. The results of the research indicate that the development of Katniss Everdeen as a character is a product of the socioeconomic power struggle within the society, both coming from the socioeconomic classes and the two presidents in Panem.